Effects of Extraction Solvents on the Yield and Physicochemical Properties of Mangifera indica L. Seed Oil - NWAOKOBIA, K; IDIBIE, C. A.; OGBORUR. O.; OKOLIE, P. L. (Dr. Chinmay Pandya, 2018)
The extraction of oil from mango seeds was investigated using a Soxhlet Extractor. Mango seeds were collected, dried and grounded into powder.  Hexane and ethanol were used to extract the oil at varying time of extraction of 4, 5, 6, 7 and 8 hours, respectively. Result shows that yield is time dependent, as increase in time of extraction results into increase in yieldwhere the least time of 4hrs yielded an average of 4.00 % and 8hrs yielded an average of 13.06 % for hexane. While the use of ethanol at 4hr and 8hrs only yielded 1.99 % and 8.22 %.Thus the use of hexane achieved the maximum yield (13.06 %) of oil extracted. The effects of time and extraction solvent on the yield of oil was investigated by using a 22 factorial design and, result shows that factor 'A' which is time, produces the greatest effect (7.665) in the yield of mango than factors 'B' (3.335) being solvent and 'AB'(1.335) being interaction between solvent and time. The effect of the extraction solvent on the physicochemical properties was also investigated where theoil extracted with hexane was found to possess better overall quality than the ethanol extracts, asits acid value, saponification value, ester value, refractive index and specific gravity were 5.61mgKOH/gOil, 207 mgKOH/gOil, 201.39mgKOH/gOil, 1.443 and 0.909, respectively as against 30.30mgKOH/gOil, 205 mgKOH/gOil, 174.70mgKOH/gOil and 0.909, respectively of ethanol. The results didn't only show that hexane gives a higher yield of oil than ethanol but also revealed that hexane is a much better solvent for the extraction of mango seed oil.